Strategic Architecture Formulation At Hotel ABC - Wardiman, Ivan Godang; Syafrizal, Syafrizal (Green Publisher Indonesia, 2023)
The impact of this pandemic is most felt by the hotel and tourism indus-try. Almost all hotels in Indonesia have experienced a decline in revenue due to this pandemic. Hotel is a type of necessity for everyone who travels or travels. Hotel is a company managed by hotel management by providing services such as rooms, food, drinks for people who travel and are able to pay a reasonable amount according to the services provided without any special agreement in advance. The purpose of this study is to develop alternative strategies and priority strategies for ABC hotels, this study uses a mix method approach with quantitative and qualitative approaches. The result obtained is that there are 10 strategies formulated to be implemented in the next 5 years. This strategy is divided into 3 stages, namely the competency strengthening stage, the growth stage, and the performance improvement stage which is compiled in a strategic architecture. The conclusion is that the current external conditions are less favorable for ABC Hotels due to the COVID-19 pandemic. So it is necessary to design another strategy to face conditions like now